2001
DOI: 10.1006/mthe.2000.0257
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Transfection and Immune Responses to Intradermal Nucleic Acid Vaccination Are Significantly Enhanced by in Vivo Electropermeabilization

Abstract: Naked DNA injection with electropermeabilization (EP) is a promising method for nucleic acid vaccination (NAV) and in vivo gene therapy. Skin is an ideal target for NAV due to ease of administration and the accessibility of large numbers of antigen-presenting cells within the tissue. This study demonstrates that in vivo skin EP may be used to increase transgene expression up to an average of 83-fold relative to naked DNA injection (50 microg DNA per dose, P < 0.005). Transfected cells were principally located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
113
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 45 publications
1
113
0
Order By: Relevance
“…10 In the present study, we utilized electroporation to improve transfection efficiency so that a single dosing regimen could be utilized and a much smaller application of DNA would be required. Drabick et al 16 demonstrated that electroporation enhances gene uptake into various cells in the cutaneous layer in mouse and pig. We utilized the skin specific electroporation parameters that we identified in our earlier work.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10 In the present study, we utilized electroporation to improve transfection efficiency so that a single dosing regimen could be utilized and a much smaller application of DNA would be required. Drabick et al 16 demonstrated that electroporation enhances gene uptake into various cells in the cutaneous layer in mouse and pig. We utilized the skin specific electroporation parameters that we identified in our earlier work.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that if the applied electrical field is of sufficient strength and intensity the dielectric index of the cell membrane is exceeded, causing transient pores to open in the lipid bilayer thereby increasing the permeability of the cells to large molecules. 16 We have demonstrated that by optimization of the electroporation parameters transfection efficiency can be improved in murine cutaneous wounds. 17 For the current study, we used the diabetic mouse BKS.Cg-m homozygous (Lepr db /Lepr db ) as a wound-healing model.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The studies on the application of electroporation-mediated gene transfer to larger animals are ongoing. 39,40 Recently, it has been reported that local gene transfer could result in a systemic therapeutic effect without systemic elevation of the therapeutic protein. 19,41 Further investigation on the mechanism responsible for these phenomena may help to develop the clinically relevant protocol for electroporation-based gene delivery strategy for the treatment of human RA.…”
Section: Discussionmentioning
confidence: 99%